A new C & I for sustainable forest management. Issue 1 (July 2021) - Supratman,; Alam, S; Sahide, M A K; Sabar, A; Makkarennu,; Hasannudin, D A L
Abstract: According to the biophysical area, the government has set the land use of forest areas to be managed for specific management purposes. The implication is that the Criteria and Indicators (C&I) of sustainable forest management are arranged fractionally, based on the forest area's function. This study aims to analyze the effectiveness of the application of C&I for sustainable forest management in conservation forests in the upstream area of the Jeneberang watershed in Gowa Regency. Field observations, interviews, focus group discussions, workshops, and documentation study conducted to collect primary and secondary data. The analysis conducted by the research were (1) Socio-Economic, (2) Landscape Change, (3) Activity-Based Management and (4) Policy Analysis. The results found the application of C&I of sustainable forest management based on forest function is ineffective because the forest area is an inseparable landscape unit, so the management unit should not be separated. Therefore, forest areas' land use should be reconstructed based on the function of forest area (fractional) to "landscape-based watershed landscape". C & I in measuring sustainable forest management performance should also be hierarchically structured interconnected input, outputs, outcomes, and impact indicators.